Pengaruh Audit Operasional Tehadap Efektivitas Pelaksanaan Dana Bantuan Operasional Sekolah pada Inspektorat Kota Sukabumi - Adisty, Dhea (Jurnal Akuntansi UMMI, 2021)
School operational funds as a component of the government is in need of financial expenditure management through the application of a good control and to measure the effectiveness of the Operational Assistance Fund, local governments through regional inspectorate needs to carry out operational audits that cover all aspects of the operational management of the School Operational Assistance Fund.Operational inspection activity should be beneficial for many public organizations have to support the smooth implementation of the Operational Assistance Fund in the future. The purpose of this study was to determine the operational audit, the effectiveness of the implementation of Operational Support at SMP's in Sukabumi and the influence of operational inspectorate to audit the effectiveness of the School Operational Assistance.The method used in this study is a quantitative method.As for the relationship between variables is causal or associative causal shows the influence of independent variables on the dependent variable.Equipment statistical test used to determine how these effects by using simple regression analysis.The tests are certainly needed the data, in this case the data collection techniques used were interviews and questionnaires. Based on the research that has been done shows that the operational audit on the Inspectorate Sukabumi been implemented properly / adequately.While the School Operational Assistance Fund in Sukabumi as a whole has performed quite effectively.Based on the hypothesis testing shows that there is a significant and positive effect of the operational audit of the effectiveness of school operational funds in Sukabumi Inspectorate, and the influence of the variable operational audit amounted to 51.4%.